Entrepreneurship-Based Multicultural Education: Fostering Batak Toba Cultural Awareness and Entrepreneurial Creativity in Jagung Kindergarten Children, Tampahan District - Sitompul, Rosalinda Septiani; Manurung, Herta; Tambunan, Bonari Hasudungan Rusmanto; Rajagukguk, Holmes; Siregar, Christyani; Togatorop, Fretty Elisabet; Pasaribu, Junjungan (Pascasarjana Universitas Mataram, 2025)
The development of the digital era has brought significant changes to children's education patterns, which not only emphasizes cognitive aspects but also demands the development of life skills, including an entrepreneurial spirit. Entrepreneurship from an early age is seen as an important strategy for instilling independence, creativity, innovation, and the courage to take risks. Integrating art, particularly traditional Batak Toba music, with entrepreneurship education offers a relevant approach to shaping a generation that is creative, productive, and rooted in local culture. However, several key issues still exist, such as children's low awareness of the economic value of artwork, minimal use of simple technology in art education, and a lack of innovation in art products aimed at business opportunities. To address these challenges, the service team from Sisingamangaraja XII University of Tapanuli implemented the program